2017
DOI: 10.2134/agronj2016.08.0483
|View full text |Cite
|
Sign up to set email alerts
|

World Phosphorus Use Efficiency in Cereal Crops

Abstract: A current estimate of global phosphorus use effi ciency (PUE) for cereal production is not available. Th e objectives of this paper were to estimate PUE for cereal crops grown in the world and to review methods for improvement. Phosphorus use effi ciency was determined using world cereal harvested area, total grain production, and P fertilizer consumption from 1961 to 2013, in addition to assumptions established from previous literature. World PUE of cereal crops was calculated using both balance and diff eren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
116
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(121 citation statements)
references
References 43 publications
0
116
2
3
Order By: Relevance
“…Historically, yield goals were used for estimating N fertilizer requirement, but their adequacy has been refuted (Raun et al, 2017a). Furthermore, Raun et al (2017) suggested the use of active sensors using vegetation indices to recommend in-season fertilizer N recommendation. A commonly used vegetation index in crop nutrient management is the normalized difference vegetation index (NDVI) (Piedallu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, yield goals were used for estimating N fertilizer requirement, but their adequacy has been refuted (Raun et al, 2017a). Furthermore, Raun et al (2017) suggested the use of active sensors using vegetation indices to recommend in-season fertilizer N recommendation. A commonly used vegetation index in crop nutrient management is the normalized difference vegetation index (NDVI) (Piedallu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorus (P) efficiency is also of concern, as it is one of the prime limiting factors for plant growth and the least mobile mineral nutrient (Goldstein, 1986; Srivastava and Singh, 2008; Joseph et al, 2015). Recovery of applied fertilizer P ranges from <10% to as high as 30% and world P efficiency averages 16% (Dhillon et al, 2017), but because fertilizer P is considered immobile in the soil and reacts with other soil minerals rather slowly, long‐term recovery of P by subsequent crops can be much higher (Roberts, 2008). For potassium (K), use efficiency by plants is generally considered higher than N and P because it is immobile in most soils and is not subject to gaseous losses like N or the fixation reactions that affect P. Efficiency of applied K can range from 20 to 80% (Roberts, 2008; Brar et al, 2011).…”
Section: Useful Conversionsmentioning
confidence: 99%
“…Due to its slow mobility and high fixation, P fertilizer‐utilization efficiency (PUE) is extremely low. For example, the global estimated PUE in cereals from 1961 to 2013 was roughly 16% (Dhillon, Torres, Driver, Figueiredo, & Raun, ). The nonutilized P tends to be retained in the uppermost soil layers and is thus prone to being lost in the runoff water and transported to surface water, with severe environmental impact (King et al., ).…”
Section: Introductionmentioning
confidence: 99%